ROLE OF SEZS IN ATTRACTING FDI IN SOUTH ASIA:A CASE STUDY OF PAKISTAN AND BANGLADESH (Contemporary Journal of Social Science Review, 2025)
Special Economic Zones (SEZs) are established around the world including South Asia to achieve the policy goals of any state regarding economic development through Foreign Direct Investment (FDI). FDI helps states to increase exports, employment generation, and many more to improve economic indicators. For developing countries, SEZs have become the prime source of attracting FDI.  Pakistan and the Bangladesh both are the South Asian States and ambitiously working on establishing SEZs to attract FDI for last two decades but they are facing political, economic and legal challenges to get their targets. A rich material is available on FDI and economic development, but much research has overlooked defining the relationship between SEZs, FDI, and economic development in developing countries of South Asia, particularly Pakistan and Bangladesh. This article mainly focuses on examining the role of SEZs in promoting FDI for economic development in Pakistan and Bangladesh. The study uses qualitative approach to analyse the importance of SEZs in attracting FDI in both countries. Data is collected through desk-research method that include books, online reports, online journals and websites. The study finds that SEZs have played a significant role in attracting FDI in Pakistan and Bangladesh. The study also highlights the challenges faced by SEZs in both countries, including infrastructure constraints, bureaucratic hurdles, and security concerns. The article concludes with the policy recommendations that suggest strategies to increase the effectiveness of SEZs in increasing FDI in South Asia.